(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
If we traced the textual focus that ruled the borders of Al-Hasnawi’s text, and deepened his hopes with the constituent idea, we would find it mixed and coherent within the hidden code in the spirit of the text, and this is what made his text extended within the paths of the text that gather meaning in depth instead of flatness. The poet defined the richness of the text through the structures of his text. stylistic, as he was able to employ it as an idea of vision; In order to define the flow of language and its stylistic nature according to this vision, and this is an intellectual, cultural and cognitive energy that he adopted in drawing the features of his poetic text.The poet was able to write the topography of his poetic text in a revival style, subject to objective interpretation according to the eloquence of the intense language and the presence of the element of the poetic image, within the scope of the coherent focal structure to arouse the imagination of the recipient,perhaps the most important thing in his texts is how to create semantics and use them in the composition of the poetic sentence, and the composition of the mental image with sound dimensions in the modern text. Among the results that we have reached is that the Hasnawi poet is an extension of the poets of the modern era, such as (Al-Jawahiri, Mustafa Jamal Al-Din) and others. His poetry still stems from the language,the revelations raised by this language do not appear in the words, but they hide and hide in their various paths,this is what characterized his poetics and what we clearly realize in his poetic texts, as he seeks through his possession of language tools to live the depth of mental perception that coordinates between the inner feeling and the external effect, and this is what makes his poetic text possess a wide space of spiritual structures; Because it suggests to the recipient what is intended and intended..